A simulation approach towards a sustainable and efficient container terminal layout design. Issue 4 (2nd October 2021) - Abu-Aisha, Tareq; Ouhimmou, Mustapha; Paquet, Marc
ABSTRACT: Seaports are considered gateways for international maritime trade. The flow of trade and the size of containerships have been growing exponentially in the last two decades, and as a result, the exchange of containers has increased dramatically. In consequence, adapting container terminal designs is required in order to confront these new challenges more efficiently and with improved sustainability. This paper studies the effect of changing the layout of seaport terminals by taking into consideration both costs and emissions. A new design of a container terminal located in the Port of Montreal is proposed and compared with the current layout. A discrete event-based simulation approach is adopted to investigate the impact of terminal layout on economic and environmental performance. This study aims to improve the performance and handling capacity of a terminal by recommending a new layout. Computational experiments were conducted to evaluate and compare the performance of both layouts using data collected from the Port of Montreal. The results indicate that terminal layout design has a significant impact on terminal performance and emission under the configuration of different transportation modes.